(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: The maternal mortality rate (MMR) in developing countries related to anemia in pregnancy caused by iron deficiency is 40.3%. The problem of anemia in pregnancy in Indonesia often occurs due to iron deficiency as much as 62.3%. Anemia in pregnant women can increase the risk of premature birth, maternal and child death, and infectious diseases. Dates which are rich in iron can increase hemoglobin levels in anemic pregnant women. Objective: To determine the effect of providing complementary therapy with dates to pregnant women in the 1st and 2nd trimesters with anemia in the working area of the Dirgahayu Community Health Center, Pulau Laut District, Kotabaru Regency. Method: This research is a type of quantitative research, using a quasi-experimental approach with a one group pretest and posttest design without a control group. Sampling in this study was carried out using a purposive sampling method, obtaining a sample of 16 respondents. Results: The Paired T-Test showed that there was a significant difference between the results of the average hemoglobin level of respondents before treatment (10.25 ± 0.52 gr/dl) and the average hemoglobin level of respondents after treatment (10.65 ± 0.4 gr/dl) p-value = 0.02. Conclusion: There is an effect of providing complementary therapy with dates to pregnant women in the 1st and 2nd trimesters with anemia in the working area of the Dirgahayu Community Health Center